Sistematización de experiencias de enseñanza-aprendizaje en educación ambiental / Systematization of Teaching-Learning Experiences in Environmental Education - Cortez, Claudia; Fernández, Zaidy (Impacto Científico, 2020)
ResumenEste artículo expone parte del trabajo de sistematización del proceso de enseñanza-aprendizaje de la cátedra de educación ambiental, cuyo objetivo es determinar a partir de experiencias reflexionadas, las representaciones y dinámicas de construcción del conocimiento sobre la complejidad de la realidad socio-ambiental, basadas en la sistematización, que considera la participación de actores internos y externos, como método para ordenar las experiencias y darle la coherencia necesaria para mejorar las prácticas educativas. Se consideraron aspectos de la planificación, ejecución y evaluación de las actividades, donde los resultados evidencian el comportamiento de los participantes y la lógica interna de las actividades.AbstractThis article describes some of the work of systematizing the teaching-learning process in environmental education. It aims to reflect on experience and determine the representations and dynamics of constructing knowledge, building on the complexity of the socio-environmental reality; it is based on systematization, which considers the participation of internal and external stakeholders as a method to order experiences and give the coherenceneeded to improve educational practices. The aspects of planning, implementation and AbstractThis article describes some of the work of systematizing the teaching-learning process in environmental education. It aims to reflect on experience and determine the representations and dynamics of constructing knowledge, building on the complexity of the socio-environmental reality; it is based on systematization, which considers the participation of internal and external stakeholders as a method to order experiences and give the coherenceneeded to improve educational practices. The aspects of planning, implementation and evaluation of activities were considered, where results show the behavior of the participants and the internal logic of the activities.